STRATEGI PENINGKATAN PRODUKSI MINYAK: OPTIMASI SUMUR ESP, PEMILIHAN TEKANAN SEPARATOR DAN PENAMBAHAN POMPA SENTRIFUGAL DI JARINGAN PIPA LAPANGAN J SUMATERA SELATAN - Pedraza, Putri Rizkika Ramadhanti (Petro : Jurnal Ilmiah Teknik Perminyakan, 2024)
Field J, managed by PT Medco E&P Indonesia, is an old oil field in the Baturaja Carbonate Formation with a water cut of up to 99%. The objective is to maximize the reservoir capacity in Field J through various production optimization scenarios, both at the single-well level and within the pipeline network. First, a single-well model is created using software and matched until the error is less than 5%. Wells are identified based on the capacity of the existing pump relative to the reservoir capacity. If the existing pump capacity is sufficient, the Size Up method is applied. If not, a new pump design with a larger capacity is created. The optimized single-well model is then incorporated into a network simulation. Pipeline network optimization is carried out with two scenarios: reducing separator pressure and adding pumps, as well as analyzing differential pressure sensitivity to determine the optimal value. The total fluid flow rate from the initial 12 wells was 21,360.30 STB/d. After single-well optimization, the flow rate increased to 48,801.36 STB/d, an increase of 128.47%. Pipeline network optimization, by reducing separator pressure from 44 psig to 15 psig, resulted in an increase of 0.98%, from 48,111.49 STB/d to 48,518.98 STB/d. Adding pumps to the surface facilities increased the flow rate by 1.86%, from 48,518.98 STB/d to 49,422 STB/d at an optimal differential pressure of 150 psi. The simulation results indicate that the proposed production optimization scenarios can increase the fluid flow rate in Field J from 21,360.30 STB/d to 49,422 STB/d, with a percentage increase of 131.38%.